Recent Trends and Developments in Social Software International Conferences on Social Software, BlogTalk 2008, Cork, Ireland, March 3-4, 2008, and BlogTalk 2009, Jeju Island, South Korea, September 15-16, 2009. Revised Selected Papers - Breslin, John G.; Burg, Thomas N.; Kim, Hong-Gee.; Raftery, Tom.; Schmidt, Jan-Hinrik.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
BlogTalk, the International Conference on Social Software, brings together different groups of people using and advancing the Internet and its usage: technical and conceptual developers, researchers with interdisciplinary backgrounds, and practitioners alike. The focus is on social software as an expression of a culture that is based on the exchange of information, ideas and knowledge. The present volume includes 6 papers from BlogTalk 2008 as well as 11 papers from BlogTalk 2009. The areas discussed include: forms and consequences of emerging social software practices; social software in enterprise and educational environments; the political impact of social software; applications, prototypes, concepts and standards.
Keywords: Computer science; Computer Communication Networks; Information systems; Multimedia systems; Computer Science; Information Systems Applications (incl.Internet).; Computer Communication Networks; Multimedia Information Systems; User Interfaces and Human Computer Interaction; Computers and Society